JENIS DAN MANFAAT FLORA PULAU DERAWAN KABUPATEN BARAU PROVINSI KALIMANTAN TIMUR - Ni Nyoman Darsini; I .G. A. Sugi Wahyuni; A.A.K. Darmadi; Ni Nyoman Wirasiti (Environmental Research Center (PPLH) of Udayana University, 2008)
A study on identication of plants species available on Derawan Island, Berau Regency, East Kalimantan has been conducted based on exploration survey around the island between 2002-2005. The plants whicht have observed were then listed on a table, their scientific names wrre recorded, their status (whether being protected or not) were determined, and the benefits or use of the plants were also listed. From this study it can be found 45 species of 30 families. They may bring benefits for the locals as vegetables, source of medicine, providing shady spots, or decorative plants.